2017
DOI: 10.1103/physreve.95.042903
|View full text |Cite
|
Sign up to set email alerts
|

Mechanics of a granular skin

Abstract: Magic Sand, a hydrophobic toy granular material, is widely used in popular science instructions because of its non-intuitive mechanical properties. A detailed study of the failure of an underwater column of magic sand shows that these properties can be traced to a single phenomenon: the system self-generates a cohesive skin that encapsulates the material inside. The skin, consists of pinned air-water-grain interfaces, shows multi-scale mechanical properties: they range from contactline dynamics in the intra-gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In all cases, two main challenges have to be taken for flexible microbatteries: fabricate flexible electrodes from active materials having weak mechanical properties and avoid the use of liquid electrolytes, which is responsible for risk of leakage. This last issue can be solved by using solid‐state electrolytes such as polymer materials, [ 25–28 ] ion‐conductive glasses of the Li 2 O–B 2 O 5 –P 2 O 5 [ 29–32 ] and Li 2 S–P 2 S 5 [ 33,34 ] system, nitrogen‐doped lithium phosphorous oxynitride (LiPON), [ 35–39 ] lithium phosphosilicate (LiSiPON), [ 40,41 ] and lithium borophosphate (LiPONB). [ 42,43 ] The most common microbattery design is the all‐solid‐state thin‐film battery, which is composed of thin film anode, cathode, and solid or polymer electrolyte materials.…”
Section: Microbatteriesmentioning
confidence: 99%
“…In all cases, two main challenges have to be taken for flexible microbatteries: fabricate flexible electrodes from active materials having weak mechanical properties and avoid the use of liquid electrolytes, which is responsible for risk of leakage. This last issue can be solved by using solid‐state electrolytes such as polymer materials, [ 25–28 ] ion‐conductive glasses of the Li 2 O–B 2 O 5 –P 2 O 5 [ 29–32 ] and Li 2 S–P 2 S 5 [ 33,34 ] system, nitrogen‐doped lithium phosphorous oxynitride (LiPON), [ 35–39 ] lithium phosphosilicate (LiSiPON), [ 40,41 ] and lithium borophosphate (LiPONB). [ 42,43 ] The most common microbattery design is the all‐solid‐state thin‐film battery, which is composed of thin film anode, cathode, and solid or polymer electrolyte materials.…”
Section: Microbatteriesmentioning
confidence: 99%
“…That means a coexistence between its crystalline and amorphous phases at room temperature with approximately 15%-30% in an amorphous-rich phase. 22 Additionally, this study aims to investigate if the α-relaxation is linked to the local segmental motions of amorphous parts of the main chain of PEO/K 2 PtCl 6 polymer composite. Furthermore, the β-relaxation process has to be explored in the meaning of a cooperative segmental motion in the noncrystalline part or the "interphase" between the crystalline and the amorphous segments of the PEO/K 2 PtCl 6 polymer that occurs at high frequencies.…”
Section: Introductionmentioning
confidence: 99%
“…PEO was selected as a host polymer because it is semicrystalline. That means a coexistence between its crystalline and amorphous phases at room temperature with approximately 15%‐30% in an amorphous‐rich phase 22 …”
Section: Introductionmentioning
confidence: 99%
“…In literature, it has been reported that blending of PEO with PVDF , PMMA , PVP [22], polyvinyl alcohol (PVA) , polyacrylonitrile (PAN) , and so forth, improved the mobility of the charge carriers and hence, improved the conductivity of the electrolyte. In the present investigation, PEO is blended with an amorphous PMMA polymer to reduce the crystallinity which can exhibit an increase in the mobility of charge carriers inside the electrolyte . As PMMA is a mechanically weak polymer, blending with PEO leads to the formation of a large number of pores that would hinder the transport of ions in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%